Interação da citosporona-b com modelos de membrana na interface ar-água - Jaroque, Guilherme Nuñez [UNIFESP] (2023)
The study of interactions at the molecular level of compounds that have some bioactive properties with membrane models allows us to understand the bioactive-membrane mechanism of action in detail. Among these models, we can use the Langmuir monolayers, which are monomolecular films built at the air-water interface. Therefore, this work aimed to study the interaction between Cytosporone-B (Csn-B), a secondary metabolite isolated from the endophyte fungus Phomopsis sp., with Langmuir films made from six phospholipids: dipalmitoylphosphatidylcholine (DPPC) and palmitoyl-oleoyl phosphatidylcholine (POPC), as phospholipids found in erythrocyte cell membranes; dipalmitoylphosphatidylethanolamine (DPPE) and dioleoyl-phosphatidylethanolamine (DOPE), found in bacterial cell membranes; and, finally, dipalmitoylphosphatidylserine (DPPS) and palmitoyl oleoyl phosphatidylserine (POPS), found in cancer cells. To analyze the interaction effects between Csn-B and lipid monolayers, surface pressure versus area per molecule isotherms, tensiometric stability curves, surface potential isotherms, and Brewster angle micrographs (BAM) were obtained. When we analyze the surface pressure versus area per molecule isotherms, it is possible to observe that, for some films, the curve shifted to larger areas, indicating the possible incorporation of the compound into the film. However, for some unsaturated lipids, it was possible to observe a shift in the curve to smaller areas, which may indicate a possible decrease in the repulsion between the polar heads of the phospholipid. Observing the tensiometric stability tests, it is possible to conclude that there was an increase in the instability of the films with the addition of Csn-B since the surface pressure decay rate was more significant in the films with the addition of the compound. There was also an increase in the surface potential of the films after the addition of Csn-B, showing a possible ordering of the electric dipoles of the phospholipids that make up the Langmuir film. The BAM images showed the formation of some interfacial clusters for some monolayer compositions, while there were no significant changes in their morphologies for others. In short, it was possible to notice thermodynamic, structural, and morphological changes in the phospholipid films after the addition of Csn-B, in addition to observing that the chemical composition of the films ends up altering the physical-chemical phenomenon observed. We believe that such data can contribute to a possible understanding of the molecular action of substances with possible biological activities in natural lipid interfaces.